PRESERVING RELIGIOUS EXPRESSIONS OF COASTAL COMMUNITY: An Ethnographic Study of Pencak Macan in Gresik (State Islamic University (UIN) of Sunan Ampel Surabaya, 2025)
This study aims to analyse the religious expressions embedded in the local culture of the Pencak Macan among the coastal community of Gresik, East Java. The research method used in this study is qualitative research, employing an ethnographic approach combined with the study of cultural ecology in coastal communities. Data were collected through interviews, observations, document research, and focus group discussions. The informants were cultural practitioners of Pencak Macan from three sub-districts in the Gresik, namely Bungah, Sidayu, and Gresik districts. The results illustrate that Pencak Macan is a distinctive traditional procession for the coastal community of Gresik. It is a traditional art symbolizing the journey of life, particularly marriage. Featuring tigers as husbands, monkeys as wives, and Gondoruwo as conflict, it portrays the domestic trials needing patience and faith. This Gresik tradition, performed during bridal processions, emphasizes faith and piety, serving as a warning against succumbing to temptations that distort human nature.